History and Performance of STKIP Bima: Empirical Study of the Influence Organizational Culture and Communication on Lecturer Performance and Economic Welfare as Intervening Variable - Wahyuni*, Wahyuni; Burhanuddin, Burhanuddin (Universitas Syiah Kuala, 2023)
This study aims to analyze and describe the history and performance of STKIP Bima in relation to the influence of organizational culture and communication on performance with lecturers' economic welfare as an intervening variable. The instruments of this research were questionnaires and history documents of STKIP Bima and the performance achievements of lecturers in carrying out the tri dharma of higher education. The results of the study show that STKIP Bima is a tertiary institution located in Bima City and was founded in the 70s so that it has alumni who are spread out and work in various professions in Indonesia and abroad. Organizational culture and communication have a significant and positive effect on performance with the economic welfare of lecturers as intervening variables. The managerial implications of the findings of this study are that the human resource development management of STKIP Bima must be supported by a proportional and performance-based increase in economic welfare.